Answers

2015-09-29T19:54:23+05:30
According to appollonius theorem  the sum of the square of 2 sides  of a triangle is equal to twice the square of the median on the third side  plus half the square of the third side.

AB^2+AC^2=2BD^2+2AD^2
=2*(I/2 BC)^2+2AD^2
=1/2BC^2+2AD^2
THEREFORE 2AB^2+2AD^2=BC^2+4AD {1}
SIMILARLY
2 AB^2 +2BC^2=AC^2+4BE^2 {2}
2BC^2+2AC^2=AB^2+4CF^2 {3}
 ADDING 1 ,2 AND 3
4AB^2+4BC^2+4AC^2=AB^2+BC^2+4AD^2+4BE^2+4CF^2
3(AB^2+BC^2+AC^2)=4(AD^2+BE^2+CF^2)








0
2015-09-30T00:26:25+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
See diagram.

AD is the median on to BC. BE and CF are medians onto AC and AB respectively.  Draw a normal AG from A on to BC.

AB² = AG² + BG²
     = AD² - DG² +  BG²
     = AD² + (BG + DG) (BG - DG)
     = AD² + BD (BD -  DG - DG)
     = AD² + BD² -  2 * BD * DG      ---- (1)

AC² = AG² + GC² 
       = AD² - GD² + GC²
       = AD² + (GC - GD) (GC + GD)
       = AD² + DC * (2 GD + DC)
     = AD² + DC² + 2 DC * GD  --- (2)

now we obtain the Apolloneous theorem, as below.  as  DC = BD = 1/2 BC,

      AC² + AB² = 2 AD² + 2 BD²   = 2 AD² + 1/2 BC²   --- (3)

similarly we can prove that:
   BC² + BA² = 2 BE² + 2 AE² = 2 BE² + 1/2 AC²        --- (4)
   CB² + CA² = 2 CF² + 2 AF² = 2 CF² + 1/2 AB²          --- (5)

add  (3), (4) and (5) to get:
 
     2 (AB² + AC² + BC²) = 2(AD² + BE² + CF²) + 1/2 * (AB²+ AC²+BC²)

     3 (AB² + AC² + BC²)  = 4 ( AD² + BE² + CF²)

1 4 1
click on thanks button above pls;;;select best answer